Price transmission and policies in biofuels-related global networks - Karel Janda; Ladislav Krištoufek; Barbora Schererova; David Zilberman (Charles University in Prague, Institute of Economic Studies (IES), 2022)
This article investigates the connections between the prices of biofuels and many traded commodities and other relevant assets in Europe, USA and Brazil. The analysis uses a comprehensive dataset covering price data for 38 traded titles over the period 2003-2020. We utilize the minimum spanning tree approach to identify price connections in a complex trading system. Our analysis of mutual price connections discovers the major defining features of world leading biofuels markets during the period since the ground-breaking policy initiatives of the 2003 EU Transport Fuel Directive and Energy Taxation Directive. We provide characteristics of main bioethanol and biodiesel markets with respect to government policies and technical and local features of the production and consumption of particular biofuels. Despite a relatively long and dynamically evolving history of biofuels, we find that the biofuels systems in USA, Brazil and Europe do not converge towards the same pattern of relations among fossil fuels, biofuels, agricultural commodities and financial assets.
Keywords: C38; Q16; Q42; 330; ethanol; biodiesel; minimum spanning tree; energy and agricultural policies